Persistent Patient‐Level Effect of Guselkumab at Consecutive 8‐Week Dosing Visits and Over Time in Patients With Active Psoriatic Arthritis: Post Hoc Analysis of a 2‐Year, Phase 3, Randomized, Controlled Study - Philip J. Mease; Xenofon Baraliakos; Vinod Chandran; Enrique R. Soriano; Peter Nash; Atul Deodhar; Emmanouil Rampakakis; Natalie J. Shiff; Soumya D. Chakravarty; May Shawi; Joseph F. Merola; Iain B. McInnes (ACR Open Rheumatology)
Objective Group‐level analyses from the phase 3 DISCOVER‐2 trial of guselkumab demonstrated robust and durable improvements across psoriatic arthritis (PsA) domains. To specifically evaluate continuous disease control in individual patients, persistence of clinically relevant improvements was assessed, both at consecutive guselkumab dosing visits and over time. Methods Post hoc analyses included biologic‐naïve patients randomized to 100 mg of guselkumab at week 0, week 4, and then every 8 weeks (Q8W). Improvements in joint (minimal clinically important improvement [MCII] in Disease Activity Index for PsA [DAPSA; ≥7.25], clinical DAPSA [cDAPSA; ≥5.7]), skin (Investigator's Global Assessment [IGA] 0/1), and overall disease activity (patient global assessment of arthritis and psoriasis [PtGA Arthritis+Psoriasis; MCII ≥ 15 mm], PsA Disease Activity Score [PASDAS; MCII ≥ 0.8]) were assessed. Proportions of patients with maintenance of DAPSA and cDAPSA MCII at consecutive Q8W guselkumab dosing visits (ie, at weeks 4 and 12, weeks 12 and 20, etc through week 52) and patient‐level durability of response through week 100 (Kaplan‐Meier) were determined. Results Among 248 patients randomized to guselkumab Q8W, 93% to 99% maintained clinical improvement in joint disease at consecutive Q8W dosing visits through week 52 across time periods. Among guselkumab patients achieving MCII by week 24, estimated probabilities of maintenance of clinical improvement 100 weeks post achievement ranged from 68% (IGA 0/1) to 89% (PASDAS MCII). Median times to loss of improvement were not reached; estimated mean weeks of maintenance of improvement were 58.6, 52.4, 75.7, 83.6, and 76.7, respectively, for DAPSA, cDAPSA, IGA, PtGA Arthritis+Psoriasis, and PASDAS. Conclusion Guselkumab provided highly durable patient‐level improvements, both at consecutive Q8W dosing visits for joint disease activity and over time across PsA domains according to physician‐ and patient‐driven assessments.